ESG+P Evolution: A Videogame Proposal for Teaching the New ESG Concept - Nascimento, Miguel; Nascimento, Gabriel; Parreiras, Marcus; Magalhães, Marcos; Xexéo, Geraldo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This article presents a proposal for a digital game that aims at teaching sustainability concepts. With technological advances, the use of digital games as a form to keep students engaged in learning a new topic has become a viable possibility to facilitate teaching. The game simulates the management of a company, in which the player must make decisions pertaining to Environmental, Social, Governance, and People dimensions. The purpose of this game is to teach students real concepts of organization sustainability through its narrative and gameplay.